A 0.35μm CMOS UWB-inspired bidirectional communication system-on-chip for transcutaneous optical biotelemetry links - De,Marcellis A; Stanchieri,GDP; Palange,E; Faccio,M; Constandinou,T (IEEE, 2019)
In this paper we report on the fabrication, implementation and experimental characterization of an integrated bidirectional communication System-on-Chip (SoC) for transcutaneous bidirectional optical biotelemetry links. The proposed architecture implements a UWB-inspired pulsed coding technique and contains a transmitter and a receiver to achieve a simultaneous bidirectional link. The transmitter generates sub-nanosecond current pulses to directly drive off-chip pulsed vertical cavity semiconductor lasers by means of a digital data coding subsystem and all the needed bias and driving circuits. On the other hand, the receiver manages off-chip fast Si photodiodes and includes signal conditioning, detection and digital data decoding circuits to support high bit rate and energy efficient communication links. The entire solution designed at transistor level has been fabricated in AMS 0.35µm standard CMOS technology into a compact silicon footprint lower than 0.13mm2 employing only 113 transistors and 1 resistor. A specific PCB has been developed together with a suitable test bench implemented on Xilinx Virtex-6 XC6VLX240T FPGA board to properly evaluate the performances and the main characteristics of the ASIC. Furthermore, a 6 GHz, 20 GS/s LeCroy WaveMaster 8600A digital oscilloscope has been employed to investigate the system time response. Preliminary experimental results validated the correct functionality of the overall integrated system demonstrating also its capability to operate, also in a bidirectional mode, at bit rates up to 250 Mbps with pulse widths up to 1.2ns and a minimum total power efficiency of about 160 pJ/bit in the conditions for which the transmitter and the receiver work simultaneously onto the same chip. These results make the developed solution suitable for high performances bidirectional optical biotelemetry links to be applied, e.g., to implantable neural recording/stimulation transcutaneous platforms that generally require communication